An investigation into the performance of full BRT and partial bus priority strategies on arterial intersections and corridors - Chitauka, Friedrich Chizhyindiswe (Department of Civil Engineering, 2015)
Rapid urbanisation is a global problem affecting most developing and intermediate countries. As the world’s urban population is set to double by the year 2050, growth in urban infrastructure and services is needed but is generally lagging behind this exponential growth, especially in most African countries. It is a reality that calls for smart responses. This implies that current resources need to be used efficiently to enable them to cater for the needs of an ever increasing urban population. Smart Transport is an innovative response to the urgent mobility and accessibility needs of urban inhabitants. Bus Rapid Transit (BRT) and bus priority measures are examples of smart transport. Research into High Level of Service Bus Systems (HLSB) or more commonly known as BRT in South African settings; has shown that they can successfully improve urban mobility while simultaneously reducing congestion, energy consumption, vehicular emissions and increase transit efficiencies. BRT is defined as a rubber-tired form of rapid transit that combines stations, vehicles, services, running ways, and ITS elements into an integrated system with a strong image and identity(Barker, Alvarez, Barnes, et al., 2003). However, the relatively high capital and operating costs of full specification/feature BRT systems are prohibitive to many local authorities. In many cities where they have already been implemented, this service is often subsidised. Furthermore, the road space is a limiting factor, as many of the areas that BRT systems needs to extend into, simply cannot accommodate conventional traffic mitigation strategies such as road widening or reservation of median lanes for BRT infrastructure. In the long term, BRT has been selected as the preferred model for mass urban transit by government i.e. all of South Africa’s major centres are in the process of implementing BRT systems. However, there is wide range of individual bus priority measures such as Bus Signal Priority (BSP) which have been used to improve public bus performance on urban corridors around the world. An opportunity exists to find alternative ways to extract maximum benefits of full specification/feature BRT. Hence the fundamental question this thesis will seek to answer is: Is it possible to reap the performance benefits of a full specification BRT system or full bus priority by implementation of partial Bus Priority Schemes at strategic locations along transit routes? Literature reviewed shows that; the full-feature BRT model in South Africa (SA) was adopted without being subjected to a process of due diligence and objective evaluation at the time. Enhanced bus systems that do not exhibit all the prescribed features of a full-feature BRT are dismissed as "BRT-lite" by proponents of the full-feature BRT model such as the Institute for Transportation and Development Policy (ITDP). The high levels of poverty among users, poor urban spatial form and financially constrained local authorities has brought the appropriateness of full-feature BRT for along SA's urban arterials into question. This roll-out of these full schemes has drawn criticism from institutions such as the World Bank who argue that the challenge in improving quality public transportation in SA lies in its access and affordability (Wood, 2014). This criticism is in light of the fact that Lagos BRT which is widely categorised as BRT-lite has demonstrated that improvements to public bus performance can be achieved in constrained African urban centres with less infrastructure and cheaper cost. Similarly, many North American cities have improved the performance of their public bus operations by using combinations of bus priority measures which are deemed most relevant for their local contexts rather than implementing full-feature BRT systems. The primary aim of this research is determine the effectiveness of alternative or partial bus priority measures compared to the baseline scenario and full priority. The study area chosen is Klipfontein Road in Cape Town (CT).